HPLC-UV METHOD APPROACH FOR THE ANALYSIS AND IMPURITY PROFILING OF CAPTOPRIL - CÂRJE, Anca Gabriela; BALINT, Alina; ION, Valentin; POP, Anca Lucia; MUNTEAN, Daniela-Lucia; SABĂU, Raluca; IMRE, Silvia (Studia Universitatis Babeș-Bolyai Chemia, 2019)
The aim of the study was to propose an improved HPLC/UV method for captopril impurity profiling based on forced degradation studies. Material and methods: the HPLC-UV analyses were performed on a Luna C18 column at 50 0C by using a mobile phase consisting of phosphoric acid 15 mM and acetonitrile at 210 nm. Results and discussions: an HPLC method with superior characteristics to one described in the European Pharmacopoeia for captopril impurities profiling was proposed. The main degradation product of captopril was captopril disulfide (Impurity A), the concentration of which increases in all the conditions of forced degradation, except thermal degradation. UV light has led to the highest number of unknown impurities, but the oxidative degradation presented the highest rate of degradation (>88%). A total of 15 unknown impurities have been observed with significant area (>0.50%), who were not initially present in the captopril sample. Conclusions: The proposed HPLC method can be successfully applied in pharmaceutical analysis laboratories as a stability indicating method of captopril, allowing the separation of official impurities A, B, C, D and E and those formed under forced degradation conditions.